2020
DOI: 10.1101/2020.09.11.293167
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reorganization of the neurobiology of language after sentence overlearning

Abstract: There is a widespread assumption that there are a static set of ‘language regions’ in the brain. Yet, people still regularly produce familiar ‘formulaic’ expressions when those regions are severely damaged. This suggests that the neurobiology of language varies with the extent of word sequence learning and might not be fixed. We test the hypothesis that perceiving sentences is mostly supported by sensorimotor regions involved in speech production and not ‘language regions’ after overlearning. Twelve participan… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 191 publications
(235 reference statements)
0
5
0
Order By: Relevance
“…The dorsal striatum has been implicated in learning through practice, particularly habit formation ( Skipper et al, 2020 ; Yin and Knowlton, 2006 ). A number of groups, including us, have hypothesised that the striatum is a brain region where we might expect to see neural differences in children with DLD ( Krishnan et al, 2016 ; Ullman et al, 2020 ; Ullman and Pierpont, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dorsal striatum has been implicated in learning through practice, particularly habit formation ( Skipper et al, 2020 ; Yin and Knowlton, 2006 ). A number of groups, including us, have hypothesised that the striatum is a brain region where we might expect to see neural differences in children with DLD ( Krishnan et al, 2016 ; Ullman et al, 2020 ; Ullman and Pierpont, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…In accordance, a series of behavioural studies has suggested that sequential learning in the linguistic and non-linguistic domains is affected in children with DLD ( Hsu and Bishop, 2014 ; Lum et al, 2014 ; but see West et al, 2018 ; West et al, 2021 ). In studies that probe complex sequential production in the vocal domain, the dorsal striatum is implicated ( Rauschecker et al, 2008 ; Simmonds et al, 2014 ; Skipper et al, 2020 ). The striatum is structurally and functionally connected to regions associated with language production, with the head of the dorsolateral caudate nucleus receiving inputs from inferior frontal cortex, and the putamen receiving inputs from motor, premotor, and supplementary motor cortex ( Alexander et al, 1986 ; Jarbo and Verstynen, 2015 ; Lima et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In accordance, a series of behavioural studies has suggested that sequential learning in the linguistic and non-linguistic domains is affected in children with DLD (Hsu & Bishop, 2014;Lum et al, 2014; but see West et al, 2018West et al, , 2021. In studies that probe complex sequential production in the vocal domain, the dorsal striatum is implicated (Rauschecker et al, 2008;Simmonds et al, 2014;Skipper et al, 2020). The striatum is structurally and functionally connected to regions associated with language production, with the head of the dorsolateral caudate nucleus receiving inputs from inferior frontal cortex, and the putamen receiving inputs from motor, premotor and supplementary motor cortex (Alexander et al, 1986;Jarbo & Verstynen, 2015;Lima et al, 2016).…”
Section: Dldmentioning
confidence: 95%
“…The dorsal striatum is important for habitual and sequential learning (Graybiel & Grafton, 2015;Yin & Knowlton, 2006), and we hypothesise that it may play an important role in the acquisition of language because of the complexity of sequencing required for language. Indeed, in studies that probe complex sequential production in the vocal domain, the dorsal striatum is implicated (Rauschecker et al, 2008;Simmonds et al, 2014;Skipper et al, 2020). Additionally, a series of behavioural studies has suggested that sequential learning in the linguistic and non-linguistic domains is affected in children with DLD (Hsu & Bishop, 2014;Lum et al, 2014; but see West et al, 2018West et al, , 2021.…”
Section: Quantitative Mri Reveals Differences In Subcortical Microstructure In Children With Dldmentioning
confidence: 99%
See 1 more Smart Citation